1990
DOI: 10.1104/pp.94.4.1547
|View full text |Cite
|
Sign up to set email alerts
|

C and N Mobilization from Stalk and Leaves during Kernel Filling by 13C and 15N Tracing in Zea mays L.

Abstract: The sink capacity of the stalk in Zea mays L. (cv DEA) during the elongation period was previously investigated with 13C and 15N tracing. The chase experiment described here demonstrates the different behavior of intermediary reserves for C and N remobilization until full maturity of the kernels. Carbon incorporated during stalk elongation participated mainly in cellulose formation in vegetative organs appearing after the labeling period; the remobilization to kernels was low (0.5%). Soluble carbohydrates and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
70
0
7

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 21 publications
3
70
0
7
Order By: Relevance
“…Overall mean to seed formation (Cliquet et al 1990, Patrick and Offler 2001, Masclaux-Daubresse and Chardon 2011. Our findings, which identified the relationship between seed germination parameters and seed carbon and nitrogen concentration, were similar to those of Frenne et al (2011), who found that the seed carbon concentration had a stronger effect on GP and MGT than the effect observed in seed nitrogen concentrations and C/N ratios.…”
Section: Characterssupporting
confidence: 69%
“…Overall mean to seed formation (Cliquet et al 1990, Patrick and Offler 2001, Masclaux-Daubresse and Chardon 2011. Our findings, which identified the relationship between seed germination parameters and seed carbon and nitrogen concentration, were similar to those of Frenne et al (2011), who found that the seed carbon concentration had a stronger effect on GP and MGT than the effect observed in seed nitrogen concentrations and C/N ratios.…”
Section: Characterssupporting
confidence: 69%
“…Our specific questions are: (1) whether flowers obtain photosynthates assimilated in the leaves on the current-year shoots to which they are attached, (2) whether the fruits obtain photosynthates assimilated in the leaves on the current-year shoots developed on the fruiting 1-year-old shoot, and (3) which current-year shoots on a fruiting 1-year-old shoot are effective for fruit maturation. To answer these questions, we conducted a tracing experiment using isotope-labelled CO 2 , a popular technique with which to examine the movement of photosynthate in a plant body (Rabideau and Burr 1945;Hartt et al 1963;Geiger and Swanson 1965;Hartt 1965;Hansen 1967Hansen , 1969Davis and Sparks 1974;Steer and Pearson 1976;Takeda et al 1980;Cliquet et al 1989Cliquet et al , 1990Deléens et al 1994). …”
Section: Introductionmentioning
confidence: 99%
“…Starch, soluble proteins, soluble sugars and amino-acids were extracted and purified according to [8,14]. 200 mg of lyophilized powder was suspended with 5 mL of a ternary mixture (methanol/chloroform/water; 12/5/3) for 30 min at ambient temperature, centrifuged for 10 min at 2 000 g (Jouan MR 22i, France).…”
Section: Extraction and Purification Of C And N Metabolites From Sapwmentioning
confidence: 99%